Nutrition Education for Young Children as a Means of Preventing Stunting in KB Al Mutchtaddin - Sumarni Sumarni; Agus Salam; Aris Iwansyah (PT. Pusmedia Group Indonesia, 2026)
The background of this study is the high risk of stunting among young children due to poor dietary habits and unsanitary living conditions, necessitating the development of educational interventions by the Al Mutchtaddin Family Planning Clinic as a preventive measure. The objective of this study is to explore and evaluate the implementation of nutrition education at KB Al Mutchtaddin, as well as to assess the effectiveness of various nutrition strategies in improving children’s knowledge, eating behaviors, and healthy lifestyle habits to prevent stunting. This study employs a qualitative method using a case study approach. Research data sources included teachers, the school principal, activity documentation, and results of direct observations during the nutrition education program. Data collection techniques were conducted through participatory observation, in-depth interviews, and photo documentation as well as activity records. The data were then analyzed using interactive analysis techniques, which included data reduction, data presentation, and repeated conclusion drawing until valid and contextual findings were obtained. The research findings indicate that Al Mutchtaddin Kindergarten has effectively implemented six nutrition education strategies: integrating nutrition content into daily lessons, hands-on activities, mini-outdoor activities and educational games, fostering healthy hygiene habits, a fruit and vegetable Market Day, and the provision of supplementary meals (PMT). These interventions have had a positive impact on improving children’s knowledge of healthy foods, changing eating behaviors, personal hygiene, and collaboration with parents, which tangibly supports efforts to prevent stunting from an early age.